Artificial Intelligence and Human-machine symbiosis in Public Employment Services (PES): Lessons from Engineer and Trade Unionist, Professor Michael Cooley. Issue 13 (2021) - Organ, John; O'Neill, Brenda; Stapleton, Larry
Abstract: This paper serves as an introduction to a problem statement for the task of designing a digital ecosystem of public employment services(PES) supported by human-machine processes. It looks at AI and algorithms and the nature of their usage in PES and, also, how, by aligning with the Human Centered ethos of Professor Michael Cooley PES can be improved for the benefit of society. As a basis from which to start, this paper shines a light on an ongoing Horizon 2020 funded collaborative project called HECAT – Disruptive Technologies Supporting Labour Market Decision Making which started from February 2020 and runs to July 2023. The HECAT project is co-ordinated by Waterford Institute of Technology and supported by partners across Europe. It has been worked on by colleagues of the authors and is concerned with the development of new technologies that valorise the PES customer. It aims to improve the PES user experience by leveraging AI and algorithms to provide real-time evidence-based insights to improve services. Professor Michael Cooley founded, with many others, the Human-Centred Systems (HCS) movement. The HCS approach valorises human tacit knowledge and strives to augment but not replace the work of the human with technology using socially useful production for the benefit of society. This paper synthesises the work of HECAT research so far and similar works so far. This work embodies new trans-disciplinary research at the convergence point of artificial intelligence and the social sciences which is, in this paper, viewed through the lens of the collective works of Professor Michael Cooley.